PERENCANAAN ULANG TATA LETAK FASILITAS DI LANTAI PRODUKSI PRODUK TEH HIJAU DENGAN METODE FROM TO CHART UNTUK MEMINIMUMKAN MATERIAL HANDLING DI PT. RUMPUN SARI MEDINI - Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2011)
PT. Rumpun Sari Medini early represent company which process green tea leaf sprout become dry tea which later then re-sold at company - company of other tea like: Sosro, 2 Forceps, and also PT. Rumpun Sari Medini with the existence of addition of new machine amount production floor, causing to arrange floor situation produce green tea become less arranged better and cause material of handling required become more, eating expense and time, and also larger ones energy. Evaluated from arranging facility situation produce PT. Rumpun Sari Medini, trouble-shooting here solving by using method of From Chart to with Facility Location Layout and software running (FLL), in this method determined travelled distance frequency between room, and also determined also degree of contiguity between room by using Activity Relationship Chart (ARC). ResultL of processing with FLL running three measurement of distance method, Rectilinear Distance, Squared Euclidean Distance and of Euclidean Distance seen from best contiguity to entire/all part of production and also possibility do the proposal layout can be applied with condition of which in fact field, got most minimum contribution value that is Euclidean Distance with contribution value equal to 115.894,32. Here also determined degree of contiguity between room by using Activity Relationship Diagram (ARC). Later;Then from proposal of layout pursuant to result of analysis of ARC and of running FLL with same method, Euclidean Distance transfer 2 department yield smaller contribution value 95.459,72 so that decided layout result of analysis of ARC weared as proposal layout. Keywords: Layout, Activity Relationship Chart (ARC), Facility Location and Layout (FLL)